The Middle Persian Title of Khusraw Parvīz’s Commander-in-Chief - Paola Orsatti (Orientalia Suecana)
The present article aims to reconstruct one of the titles borne by Khusraw Parvīz’s commander-in-chief (sipahbad), generally known to the sources as Shahr-barāz, ‘The Wild Boar of the Kingdom’. The title that is the object of this study is variously given as Farrukhān, Farruhān, and Khurrahān in Islamic sources, and as Khoṙeam in an Armenian chronicle. Two New Persian literary texts, the Shāhnāma (composed between the late tenth and early eleventh century) and the Mujmal al-tawārīkh wa’l qiṣaṣ (begun in 520/1126), offer two forms that certainly originate from a misreading of the title in its Pahlavi and Arabo-Persian spellings, respectively. Such erroneous forms, however, are useful for ascertaining the original form of the title. Only Farrahān, meaning ‘glorious, endowed with farr/farrah’, an adjective derived from farrah ‘glory, divine charisma’ and the adjectival suffix ‑ān, matches all the attested forms.